دراسة بعض عوامل الضغط المهني التي تؤثر على الأداء الوظيفي لمدربي كرة القدم - يونس,أحمد عماد الدين (University of Eloued جامعة الوادي, 2024)
ملخص: هدفت هذه الدراسة إلى معرفة ما يعانيه مدربو كرة القدم في الجزائر من ضغوط مهنية تؤثر على أدائهم المهني وذلك باتباع المنهج الوصفي، وأجريت الدراسة على مجموعة من مدربي كرة القدم لرابطة باتنة الجهوية تم اختيارهم بطريقة قصدية، وتم استخدام مقياس مصادر الضغوط المهنية للمدرب الرياضي لمحمد حسن علاوي. وتوصلت الدراسة إلى أن مهنة التدريب تعاني الكثير من المشاكل والصعوبات المنحصرة في اللاعبين والفريق الرياضي والإدارة والمشجعين. Abstract: This study aimed to know the professional pressures that football coaches in Algeria suffer from affecting their professional performance by following the descriptive approach, and the study was conducted on a group of football coaches of the Batna Regional League who were deliberately chosen, and the measure of sources of professional stress was used for the sports coach of Mohamed Hassan Allawi. The study found that the coaching profession suffers from many problems and difficulties confined to the players, sports team, management and fans.
Keywords: الضغوط المهنية; المدرب الرياضي; كرة القدم; الأداء الوظيفي; Professional pressures; Sports Trainer; football; Functionality